2007
DOI: 10.1097/mnh.0b013e3281ca6ffd
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of fibroblast growth factor 23 in a bone–kidney axis regulating systemic phosphate homeostasis and extracellular matrix mineralization

Abstract: FGF23 discovery has uncovered primary regulatory pathways and new systems biology governing bone mineralization, vitamin D metabolism, parathyroid gland function, and renal phosphate handling. FGF23 assessment will become important in diagnosing hypophosphatemic and hyperphosphatemic disorders, for which pharmacological regulation of FGF23 levels may provide novel treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
1
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 74 publications
2
70
1
9
Order By: Relevance
“…2) FGF23 is produced mainly in osteoblasts in the early stage, but comes to be seen predominantly in osteocytes in the later stages of metaphyseal trabeculae and cortical bones. Sclerostin and FGF23 have been known as osteocyte-derived factors (22,28,35,39,41,42). However, this study revealed the different distribution of sclerostin/FGF23 between the close and distant regions of metaphyseal trabeculae.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…2) FGF23 is produced mainly in osteoblasts in the early stage, but comes to be seen predominantly in osteocytes in the later stages of metaphyseal trabeculae and cortical bones. Sclerostin and FGF23 have been known as osteocyte-derived factors (22,28,35,39,41,42). However, this study revealed the different distribution of sclerostin/FGF23 between the close and distant regions of metaphyseal trabeculae.…”
Section: Discussioncontrasting
confidence: 47%
“…Although Fgf23 mRNA was found in several tissues (1,21,34), it was most abundantly expressed in bone (41). As a circulating growth factor, FGF23 inhibits phosphate reabsorption and 1α,25(OH) 2 D 3 production in the kidney (22), thus acting on serum homeostasis of phosphate and calcium. In brief, sclerostin and FGF23 are secreted by osteocytes and appear to be involved in bone metabolism in adult stages, i.e., are involved in normal bone remodeling and serum mineral balance.…”
Section: Methodsmentioning
confidence: 99%
“…However, the major player of the bone-kidney axis controlling phosphate homeostasis has been shown to be fibroblast growth factor 23 (FGF23). FGF23 acts as a phosphaturic factor by the same mechanism of action as PTH, downregulating the co-transporters NaPi2a and NaPi2c in the kidney after binding to its receptor, FGFR1, in the presence of Klotho (9)(10)(11). FGF23 also decreases 1,25(OH) 2 D synthesis in the proximal tubules by direct inhibition of the 1a-hydroxylase enzyme (9,10,12).…”
Section: Introductionmentioning
confidence: 99%
“…FGF23 is predominantly produced and secreted by osteocytes in bone (9,10). This process is positively regulated by 1,25(OH) 2 D, via a vitamin D response element in the fgf23 promoter (9,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…FGF23 downregulates matrix proteins, such as osteocalcin and sialoprotein, which are both required for osteogenesis and reduces 1-alpha-hydroxylase vitamin D levels, resulting in hypophosphatemia, renal phosphate wastage and osteomalacia (Liu et al 2007, Tenenhouse 2007.…”
mentioning
confidence: 99%